Application of the Health Belief Model to customers' use of menu labels in restaurants. (1st April 2018) - Jeong, Jin-Yi; Ham, Sunny
Abstract: Some countries require the provision of menu labels on restaurant menus to fight the increasing prevalence of obesity and related chronic diseases. This study views customers' use of menu labels as a preventive health behavior and applies the Health Belief Model (HBM) with the aim of determining the health belief factors that influence customers' use of menu labels. A self-administered survey was distributed for data collection. Responses were collected from 335 restaurant customers who experienced menu labels in restaurants within three months prior to the survey. The results of a structural equation model showed that all the HBM variables (perceived threats, perceived benefits, and perceived barriers of using menu labels) positively affected the customers' use of menu labels. Perceived threats were influenced by cues to action and cues to action had an indirect influence on menu label use through perceived threats. In conclusion, health beliefs were good predictors of menu label use on restaurant menus. This study validated the application of the HBM to menu labeling in restaurants, and its findings could offer guidelines for the industry and government in developing strategies to expand the use of menu labels among the public.